Dynamic programming model for obtaining optimal production schedule of palm oil production - Ozah, Obeten Bright; Biu, Emmanuel Oyinebifun; Ikpan, Okim Iyang; Jasper, Okoi Essien; Effiong, Eyo Eyo (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2023)
Production planning managers face the challenge of determining how best to schedule production to meet their demands. In many production environments, production plans are driven by customer requirements as exogenously determined by the sales and marketing division of the firm. In most practical contexts, demands usually do not follow a linear model, hence, the linear programming technique will be inappropriate and prove abortive, in such cases, dynamic programming may be required to adequately model the planning schedule in other to achieve optimal decision that minimizes the production cost. Consequently, there is discretion by the producer to accept or deny production orders and he will only take orders that will optimise production. This research uses dynamic programming to model Palm Oil data to determine the optimal decision that gives the best production schedule. The result shows that for the entire period of production under study, the production schedule that minimizes the production cost and satisfies the demand from January to December is obtained by producing 970 units in January and 720 units in October. This gives a minimum production cost of ₦812,390.